Kidney Function Does Not Modify the Favorable Quality of Life Changes Associated With Revascularization for Coronary Artery Disease: Cohort Study - Matthew T. James; Stephen B. Wilton; Fiona M. Clement; William A. Ghali; Merril L. Knudtson; Zhi Tan; Marcello Tonelli; Brenda R. Hemmelgarn; Colleen M. Norris (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2016)
BackgroundAlthough patients with kidney disease have potential to benefit from revascularization, they are also at higher risk of complications, which may affect quality of life. Methods and ResultsWe studied a cohort of 8198 adults who underwent coronary angiography in Alberta, between 2004 and 2008, and completed health‐related quality‐of‐life (HR‐QOL) surveys. Changes in HR‐QOL measures were most favorable among patients who received coronary artery bypass graft (CABG), but did not significantly differ by kidney function within groups of patients who received CABG, percutaneous coronary intervention (PCI), or medical therapy (P value for interaction between estimated glomerular filtration rate [eGFR] and revascularization status >0.10 for all outcomes). Among those who received CABG, the adjusted mean EuroQol 5 dimensions (EQ‐5D) utility score for those with eGFR >90 mL/min per 1.73 m2 increased by 0.11 (95% CI, 0.09–0.14) and for those with eGFR <30 mL/min per 1.73m2 by 0.13 (95% CI, 0.05–0.21). The adjusted mean EQ‐5D utility score also increased similarly at all levels of eGFR for those who received PCI and for those who received medical management. Mean changes in Seattle Angina Questionnaire (SAQ) scores were also similar across all levels of eGFR within each treatment group for the quality of life, angina frequency, angina stability, physical limitations, and treatment satisfaction domains of the SAQ. Among those who received CABG, the adjusted mean SAQ quality of life score for those with eGFR >90 mL/min per 1.73m2 increased by 22.1 (95% CI, 18.5–25.7) and for those with eGFR <30 mL/min per 1.73m2 by 14.0 (95% CI, 2.31–25.63). ConclusionsChanges in HR‐QOL do not vary by kidney function among patients selected for CABG, PCI, or medical management of coronary disease.